Identification of Chromobacterium violaceum by MALDI-TOF mass spectrometry in blood culture - Araújo, Max Roberto Batista; Wolf, Vanessa; Seabra, Luisa Ferreira (Clinical and Biomedical Research, 2018)
Report of Chromobacterium violaceum isolation from blood culture. Identification by MALDI-TOF mass spectrometry. Relevant report due to the site affected, infection severity, and importance of correct and rapid identification for a successful treatment and lower risk of morbidity and mortality. Keywords: Chromobacterium; blood Culture; sepsis; spectrometry, mass; Matrix-Assisted Laser Desorption-Ionization